Vocabulary Demands of Informal Spoken English Revisited: What Does It Take to Understand Movies, TV Programs, and Soap Operas? - Ha, Hung Tan (Frontiers in Psychology, 2022)
The article presents a methodological update on the lexical profile of informal spoken English with the emphasis on movies, television programs and soap operas. The study analyzed Mark Davies’s mega-corpus with data containing approximately 625 million words and employed Paul Nation’s comprehensive and up-to-date British National Corpus/ Corpus of Contemporary American English (BNC/COCA) wordlists. Data from the analyses showed that viewers would need a vocabulary knowledge at 3,000 and 5,000 word-frequency levels to understand 95% and 98% of the words in scripted dialogs, respectively. Soap operas were found to be less lexically demanding compared to TV programs and movies. Findings are expected to fill in the methodological gaps between vocabulary assessment and vocabulary profiling researches.